Subacute and chronic post-COVID myocarditis: diagnostics, clinical variants, treatment approaches - P. O. Savina; O. V. Blagova; D. Kh. Ainetdinova; A. V. Sedov; E. V. Pavlenko; Yu. A. Lutokhina; E. A. Kogan (Российский кардиологический журнал)
Aim. To study the mechanisms and clinical variants of subacute and chronic myocarditis after SARS-CoV-2 infection using morphological and virological studies and to develop approaches to its treatment.Material and methods. The study included 89 patients with documented coronavirus disease 2019 (COVID-19). The diagnosis of post-COVID myocarditis was established based on myocardial biopsy and/or cardiac magnetic resonance imaging (MRI) data in combination with anamnesis, increased titers of anticardiac antibodies, and other criteria. The average time of presentation after infection was 8,0 [4; 17,5] months, while the average follow-up period was 7,0 [6,0; 13,5] months. Electrocardiography, Holter monitoring, echocardiography, cardiac MRI (n=60), determination of anticardiac antibody levels, myocardial biopsy (n=38), and autopsy (n=1) were performed.Results. All patients showed an association between the onset or exacerbation of cardiac symptoms and COVID-19. The clinical variants of post-COVID myocarditis were identified: arrhythmic (n=24) with newly developed arrhythmias with normal myocardial contractility; decompensated (n=65) with newly diagnosed heart failure, including a variant developed with primary (genetic) cardiomyopathies and amyloidosis (n=10). The profile of arrhythmias in the arrhythmic variant varied from potentially life-threatening rhythm and conduction disorders (sustained ventricular tachycardia, grade II-III atrioventricular block) to infrequent supraventricular premature beats. In the decompensated variant, lymphocytic myocarditis was most often morphologically detected, while eosinophilic and giant cell myocarditis, associated with a worse prognosis, were rarer. Simultaneous development of nonbacterial thrombotic endocarditis, infective endocarditis with the development of valvular heart defects was noted. In 10 cases, myocarditis was combined with primary cardiomyopathies, AL amyloidosis. Treatment included the administration of antiarrhythmic, cardiotropic, immunosuppressive therapy (glucocorticoids 16-32 mg/day in 68,5% of patients, hydroxychloroquine 200-400 mg/day in 33,7%). In the arrhythmic type, complete arrhythmia suppression was achieved in 25% of cases, while partial in 58,3%. In one case, a pacemaker was implanted. In patients with a decompensated myocarditis, corticosteroids were effective regardless of the viral genome/proteins in the myocardium.Conclusion. COVID-19 can induce subacute and chronic myocarditis with the development of isolated arrhythmias or severe heart failure.